A rare case of advanced cervical cancer in pregnancy: clinical presentation, diagnostic challenges, and multidisciplinary management - Malakar, Abhishek; Fan, Sharon; Snowden, Benjamin; Javaid, Fizza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Advanced cervical cancer diagnosed during pregnancy is an exceptionally rare occurrence. We present a case of stage IIIC cervical squamous cell carcinoma identified during pregnancy. A woman in her early thirties in her fourth pregnancy attended maternity triage with unprovoked antepartum haemorrhage at 23+2 weeks of gestation with an irregular mass on her cervix. Colposcopic biopsy confirmed a moderately to poorly differentiated invasive squamous cell carcinoma. MRI pelvis showed parametrial invasion and pelvic lymphadenopathy, consistent with FIGO stage IIIC1 disease. Following multidisciplinary team discussion, the management plan included early delivery with steroid cover, followed by definitive chemoradiotherapy. At 32 weeks’ gestation, a caesarean section with sterilisation was performed due to severe fetal growth restriction (estimated fetal weight <3rd centile). Postnatally, the patient commenced neoadjuvant chemotherapy with paclitaxel and carboplatin, followed by definitive chemoradiotherapy consisting of external beam radiation and intracavitary brachytherapy. Post-treatment MRI demonstrated an excellent therapeutic response. Management of cervical cancer in pregnancy depends on gestational age and disease stage. This case illustrates the multidisciplinary management of advanced cervical cancer in pregnancy, balancing maternal treatment needs with fetal well-being to achieve optimal outcomes for both. This case also underscores the importance of regular cervical screening, patient education regarding its value, and careful speculum examination by experienced clinicians in pregnant women presenting with vaginal bleeding, as pregnancy can obscure critical symptoms.